Egan, Imagination In Teaching and Learning - The Middle School Years - Diem, Richard (Teaching History: A Journal of Methods, 1994)
The best analogy one could draw in preparing to teach middle school social studies classes is one that is similar to a general getting ready for a battle whose soldiers consist of a vast pool of untried individuals with a myriad of both unlimited academic talents and deficiencies who are away from home for the first time. To get the troops ready for the foray the general must understand, nurture, and draw upon the talents each individual possesses in order to overcome any trepidations they may have and to eventually conquer their foe.